How healthy are we? Narratives of experiential health from a village of Western Nepal - Subedi, Bamdev (Dhaulagiri Journal of Sociology and Anthropology, 2016)
It has become a custom citing development reports, which show remarkable progress in some of the health indicators, to signify the higher quality of life achieved over the years. The human development datasets, for instance, present impressive progress in terms of decreased mortality, increased life expectancy, higher literacy and falling poverty which is synonymous to a higher standard of living. With the amazing success in medical science, advancement in therapy and surgery, and prevention and control over some of the dangerous diseases, we are bound to believe that we have achieved much, and there is no question whether the overall health condition has been worsened in the last few decades. The real life experience of local people, however, challenges this fact and compels us to reflect on “are we really healthy than before?” Drawing from a qualitative study conducted in a district of mid-western Nepal, this paper presents people’s narratives to deepen our understanding of how people in an urbanizing village experience health. The paper recognizes the deteriorating health experience of the people which has primarily resulted from a loss of local health traditions exacerbated by the current change and development.